Behavior of the combined radial post-feeding larval dispersal of the blowflies Chrysomya megacephala and Chrysomya albiceps (Diptera, Calliphoridae) and implications for forensic entomology - Gomes,Leonardo (2007)
The aims of this work was to study the life stages of Chrysomya megacephala in a circular arena allowing the combined radial post-feeding dispersal from the center of the arena of C. albiceps and C. megacephala larvae. To determine the location of each pupa, the distance from the center, the depth and weight of each pupa formed were analyzed. For the larvae of C. albiceps, females released buried deeper than males, reaching an average depth of 10.74 cm and C. megacephala larvae presented greater average results than C. albiceps for all variables, particularly distance, which was 16.02 cm for this species and 12.30 cm for C. albiceps. C. albiceps larvae preyed on 30 C. megacephala larvae in both experiments. These results could be used in forensic entomology because the evaluation of Post Mortem Interval (PMI) was one of the most important aspects of legal medicine, and it could be underestimated if the older dispersing larvae or those that dispersed longer and faster or deeper, were not taken into account.